Evolution of Industrial Quality Parameters of Wheat during Storage in White and Colored Silo Bags: A Field-Scale Study - Bartosik, Ricardo Enrique (2024)
Over the past two decades, the silo bag system has gained popularity for storing grains and by-products under hermetic conditions. However, the impact of higher temperatures in the outer grain layer on key industrial parameters, such as wheat baking quality, remains insufficiently understood. Traditional silo bags are black on the inside and white on the outside to reflect sunlight, but colored bags, recently introduced to the market, absorb more heat, potentially warming the grain and causing damage. This study aimed to assess the effect of grain strata and bag color on grain temperature and quality under field conditions. Results showed a significant surface temperature increase in colored bags compared to white ones, approximately 3 °C, which affected the temperature of the peripheral grain layer. Moisture content slightly increased (0.2 percentage points) in the outer grain layer. However, many industrial quality parameters (protein content, P/L, W, and loaf volume) and the germination test for wheat, showed no significant differences between colored and white bags or between different strata after 120 days of storage, although the falling number increased and wet gluten decreased. These findings suggest that, despite surface temperature differences, the overall industrial quality of wheat remains unaffected by external bag coloration. The influence of ambient temperature on the peripheral layer was estimated to affect approximately 5–10% of the grain mass, indicating that adverse impacts on grain quality may go unnoticed without implementing stratified sampling techniques.